2011
DOI: 10.1111/j.1750-3841.2011.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Water Distribution in Xanthan‐Curdlan Hydrogel Complex Using Magnetic Resonance Imaging, Nuclear Magnetic Resonance Relaxometry, Rheology, and Scanning Electron Microscopy

Abstract: The combination of texture measurements and discrete noninvasive techniques was found capable of providing insightful understanding of water distribution in a gel system. These techniques may be applied to other hydrogel complexes. The XCHC system investigated has the potential to enhance freeze-thaw stability in frozen food products by minimizing syneresis due to undesirable temperature fluctuations during distribution and consumer application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
2
20
0
2
Order By: Relevance
“…Proton T 1 and T 2 measurements at a low magnetic field for hydrogels, relevant for food science, were reported by Williams et al, 313 who investigated the xanthan-curdlan systems and by Baranowska et al 314 who reported data on starch gels and starch-xanthan systems. Similar work, even more explicitly connected to foodstuffs, has been quite common.…”
Section: Synthetic Polymers In Solutionmentioning
confidence: 87%
“…Proton T 1 and T 2 measurements at a low magnetic field for hydrogels, relevant for food science, were reported by Williams et al, 313 who investigated the xanthan-curdlan systems and by Baranowska et al 314 who reported data on starch gels and starch-xanthan systems. Similar work, even more explicitly connected to foodstuffs, has been quite common.…”
Section: Synthetic Polymers In Solutionmentioning
confidence: 87%
“…The T 2 , is the decaying rate of the transverse component of the magnetization and it is an indicator of interactions between the nuclear spins (Williams, Oztop, McCarthy, McCarthy, & Lo, 2011). The difference of the molecular mobility of water and oil proton species result in significant changes in T 2 values (Hickey et al 2006).…”
Section: Water Suppression Imagesmentioning
confidence: 99%
“…Low-field nuclear magnetic resonance (NMR) technology is an effective tool to study the water status of food, mainly by determination of the proton relaxation behavior [5,6]. e relaxation process occurs through fluctuations in the magnetic field caused by random molecular motions, both rotational and translational.…”
Section: Introductionmentioning
confidence: 99%